Menemukan Makna Tawakal di Tengah Modernitas: Refleksi atas Kisah Kepasrahan Nabi Ismail dalam QS. Ash-Shaffat 102–107 - Awalia Kholifatur Riska; Ahmad Nurrohim (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
This study aims to explore the meaning of tawakal in the story of Prophet Ismail as described in Surah Ash-Shaffat verses 102–107 and to examine its relevance to modern human life. Through a thematic interpretation (tafsir maudhu‘i) and a comparative analysis between classical and contemporary interpretations, this study finds that tawakal is not merely an attitude of surrender to Allah's will, but a form of spiritual awareness that unites effort and submission. Classical exegetes such as al-Tabari, Ibn Kathir, and al-Qurtubi interpret this story as the pinnacle of obedience and total surrender of a servant to Allah's commands. Meanwhile, contemporary exegetes such as Quraish Shihab and Sayyid Quthb emphasize the reflective and psychological dimensions, that tawakal is a spiritual force that fosters inner peace amid the pressures of modern life. Research findings indicate that the value of tawakal has profound significance as a moral principle, social ethic, and spiritual therapy capable of restoring balance between rationality and faith in facing the existential crises of modern humanity.